The prevalence of primary REDs indicators and the potential role of low libido as a sign of male athlete REDs: examining prevalence and associations with established REDs indicators among Finnish Elite male athletes - Henttu, Iida (2025)
Henttu, I. 2025. The prevalence of primary REDs indicators and the potential role of low libido as a sign of male athlete REDs: examining prevalence and associations with established REDs indicators among Finnish Elite male athletes. Faculty of Sport and Health Sciences, University of Jyväskylä, Master’s thesis in Exercise Physiology, 69 p.